2017
DOI: 10.1038/s41598-017-14988-4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging cellulose synthase motility during primary cell wall synthesis in the grass Brachypodium distachyon

Abstract: The mechanism of cellulose synthesis has been studied by characterizing the motility of cellulose synthase complexes tagged with a fluorescent protein; however, this approach has been used exclusively on the hypocotyl of Arabidopsis thaliana. Here we characterize cellulose synthase motility in the model grass, Brachypodium distachyon. We generated lines in which mEGFP is fused N-terminal to BdCESA3 or BdCESA6 and which grew indistinguishably from the wild type (Bd21-3) and had dense fluorescent puncta at or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…mEGFP-PpCESA5 particle velocities under control conditions averaged 262 ± 80 (SD) nm/min (Fig. 4a,d ; Supplementary Movie S3 ), similar to the ~250–300 nm/min FP-CESA particle velocities measured in Arabidopsis seedlings 3 , 5 , 14 and slightly faster than the mean of 164 nm/min measured in B. distachyon using a different quantification method 18 . Treatment of protonemal filaments expressing mEGFP-PpCESA5 with DCB or isoxaben before imaging dramatically decreased mEGFP-PpCESA5 motility (Fig.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…mEGFP-PpCESA5 particle velocities under control conditions averaged 262 ± 80 (SD) nm/min (Fig. 4a,d ; Supplementary Movie S3 ), similar to the ~250–300 nm/min FP-CESA particle velocities measured in Arabidopsis seedlings 3 , 5 , 14 and slightly faster than the mean of 164 nm/min measured in B. distachyon using a different quantification method 18 . Treatment of protonemal filaments expressing mEGFP-PpCESA5 with DCB or isoxaben before imaging dramatically decreased mEGFP-PpCESA5 motility (Fig.…”
Section: Resultssupporting
confidence: 79%
“…In Arabidopsis, treatment with 2,6-dichlorobenzonitrile (DCB) immobilizes YFP-AtCESA6 in the plasma membrane, whereas treatment with isoxaben causes accumulation of YFP-AtCESA6 in vesicles below the membrane 14 . Although particle density was not measured, DCB reduced mEGFP-BdCESA particle velocity in Brachypodium distachyon 18 . In contrast, freeze fracture electron microscopy of protonemal filaments from the moss Funaria hygrometrica indicated that CSCs are lost from the plasma membrane after DCB treatment 35 .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…By TILLING in a mutagenized background we identified a single allele Bdcesa1 S830N . As noted by Liu et al (2017), CESA mutations in grasses are lacking, which complicates comparisons to other alleles. Gene complementation is also made difficult by the fact that the mutant allele likely encodes a functional protein product that can interact with the wild-type product.…”
Section: Resultsmentioning
confidence: 99%
“…This has been observed in real time for primary CesAs in both A. thaliana and B. distachyon, which showed similar speeds in B. distachyon mesocotyl and root, as in A. thaliana hypocotyl. This motility was not affected by latrunculin B treatment, which destabilized actin filaments, but was dampened in both species when microtubules were disrupted (Liu et al, 2017). Missense mutation in Bdcesa1, a primary wall cellulose synthase, showed reduced cellulose content and crystallinity, as do A. thaliana AtcesA1 mutants (Arioli et al, 1998;Persson et al, 2007;Brabham et al, 2019).…”
Section: Cellulosementioning
confidence: 91%